Inter-rater reliability of care home staff's proxy judgements with residents' assessments of their own health-related quality of life: an analysis of the PATCH trial EQ-5D data. (5th April 2021) - Kelly, Charlotte; Hulme, Claire; Graham, Liz; Ellwood, Alison; Patel, Ismail; Cundill, Bonnie; Farrin, Amanda; Goodwin, Madeline; Hull, Karen; Fisher, Jill; Forster, Anne
Abstract: Objectives: to compare care staff proxies with care home residents' self-assessment of their health-related quality of life (HRQoL). Methods: we assessed the degree of inter-rater reliability between residents and care staff proxies for the EQ-5D-5L index, domains and EQ Visual Analogue Scale at baseline, 3 months and 6 months, collected as part of the PATCH trial. We calculated kappa scores. Interpreted as <0 no agreement, 0–0.2 slight, 0.21–0.60 fair to moderate and >0.6 substantial to almost perfect agreement. Qualitative interviews with care staff and researchers explored the challenges of completing these questions. Results: over 50% of the HRQoL data from residents was missing at baseline compared with a 100% completion rate by care staff proxies. A fair-to-moderate level of agreement was found for the EQ-5D-5L index. A higher level of agreement was achieved for the EQ-5D-5L domains of mobility and pain. Resident 'non-completers' were more likely to: be older, have stayed a longer duration in the care home, have lower Barthel Index and Physical Activity and Mobility in Residential Care (PAM-RC) scores, a greater number of co-morbidities and have joined the trial through consultee agreement. Interviews with staff and researchers indicated that it was easier to rate residents' mobility levels than other domains, but in general it was difficult to obtain data from residents or to make an accurate proxy judgement for those with dementia. Conclusions: whilst assessing HRQoL by care staff proxy completion provides a more complete dataset, uncertainty remains as to how representative these values are for different groups of residents within care homes.